MODELING THE PURCHASE DECISION AND CUSTOMER LOYALTY MECHANISM USING AGENT-BASED SIMULATION - Tomiputra, Syafiq Mahdi; Nuraeni, Shimaditya (Journal of Business and Management, 2019)
Background: Gaining new customers costs five to 25 times more than retaining existing ones. People who have bought from a company three times are 54% more likely to buy from the same company. All of this leads up to the point that catering to existing customers increases profitability. Thus, proving the need for customer loyalty. This research has the objective of identifying the mechanism behind a customer?s purchase decision and the buildup of customer loyalty through repeat purchases. The second objective of the research is to identify the timing to launch a loyalty program in relation to the market segments proportion.Methods: Agent-based modeling is used to capture the dynamics of human interaction. The model created will be a generic model. Internal validation test is used to validate the model, and corner testing the market segment proportions to determine the timing to launch a loyalty program depending on the market segment proportions.Results: The findings of this research dictates that a person will decide to purchase if it is sufficiently affected by its factors. The research shows that there is a significant difference in optimal time to post a loyalty program depending on the proportion of the market segments.Keywords: Agent-based modeling, complex system, customer loyalty, purchase decision, simulation